Morphometry of leguminous seeds produced in different spacing - Monteiro, Shirley Santos (2019)
The production of legume seeds can be a strategy to increase the income of family farmers, as well as the improvement of soil characteristics. The objective of this work was to evaluate the morphometric characteristics of the seeds of legume species produced at different spacings. The experiment was conducted at the Federal University of Paraíba, Campus III, Bananeiras, Paraíba. The experimental design was a randomized complete block design in the 3 x 3 factorial scheme, three legume species (black mucuna, pork bean and lablab) and three spacings (0.50 x 0.50, 0.50 x 0.75 e 0.50 x 1.0 m) with three replicates. It was evaluated the physical characteristics: pod length and width, seed length and width, seed pod weight, seedless pod weight, seed weight, seed number per pod, yield, total pod weight, total weight of the seed and weight of 100 seed. The legume Bean of Pork had greater increase in morphometric performance, followed by Mucuna Preta and Lablab. The spacing did not influence the Morphometry of leguminous seeds.